The Key Role of Porphyromonas gingivalis in the Pathogenesis of Periodontitis Linked with Systemic Diseases - Bianca Maria Messina; Cristina Grippaudo; Alessandro Polizzi; Andrea Blasi; Gaetano Isola (Applied Sciences, 2025)
New technologies and tools are emerging in periodontology and oral health. Periodontitis is a chronic inflammatory condition that destroys the supporting tissues of the teeth and ultimately leads to tooth loss. As one of the most prevalent oral conditions, periodontitis endangers the oral health of 70% of people worldwide, and has been increasingly linked to various systemic diseases. In this regard, Porphyromonas gingivalis (P. gingivalis) is a key pathogen in the oral microbiome and a Gram-negative oral anaerobic bacterium that plays a key role in the pathogenesis of periodontitis. Porphyromonas gingivalis can express various virulence factors to evade innate and adaptive immunities, which causes P. gingivalis to survive and propagate in the host, destroy periodontal tissues, and contribute to systemic diseases. This narrative review aims to summarize the current knowledge on the impact of P. gingivalis in oral microbiome formation and its mechanistic links to systemic diseases such as cardiovascular disease, diabetes mellitus, rheumatoid arthritis, and Alzheimer’s disease. This review will explore the pathogenic mechanisms employed by P. gingivalis, including immune evasion, dissemination, and molecular mimicry, and evaluate the clinical and epidemiological evidence linking periodontitis with systemic health outcomes. By consolidating these insights, this review seeks to highlight the importance of periodontal health in preventing systemic diseases and propose potential therapeutic interventions targeting P. gingivalis. These findings highlight that early diagnosis and effective treatment of periodontitis, particularly targeting P. gingivalis, are essential not only to preserving oral health but also to reducing the risk and progression of systemic diseases.